Design and Demonstration of Three-Electrode Pouch Cells for Lithium-Ion Batteries. Issue 7 (14th June 2017) - An, Seong Jin; Li, Jianlin; Daniel, Claus; Kalnaus, Sergiy; Wood, David L.
Abstract : Simple three-electrode pouch cells which can be used in distinguishing the voltage and resistance in individual electrodes of lithium ion batteries have been designed. Baseline (1 mm-staggered alignment, cathode away from a reference electrode) and aligned electrodes to a reference electrode located outside of the anode and cathode were studied to see alignment effects on resistance analysis. Cells composed of A12 graphite anodes, LiNi0.5 Mn0.3 Co0.2 O2 (NMC 532 or NCM 523) cathodes, lithium foil references, microporous tri-layer membranes, and electrolytes, were cycled with cathode cutoff voltages between 3.0 V and 4.3 V for formation cycles or 4.6 V for C-rate performance testing. By applying a hybrid pulse power characterization (HPPC) technique to the cells, resistances of the baseline cells contributed by the anode and cathode were found to be different from those of the aligned cells, although overall resistances were close to ones from aligned cells. Resistances obtained via electrochemical impedance spectroscopy (EIS) and 2D simulation were also compared with those obtained from HPPC.